Cognitive and Affective Well-Being Differences in Subjective and Objective Socioeconomic Status Groups - Diržyte, Aiste; Patapas, Aleksandras (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: This study aimed at identifying the relationship between socioeconomic status and psychological well being in the Lithuanian population. Background: Socioeconomic status implies that not all individuals have equal opportunities to achieve their goals, because not everyone has equal access to education, health, even business support services, and the psychological well-being of some may be significantly reduced solely by lack of material resources. Method: The main method of research in the article is an interview method at the respondent's home. Also, various assessment tools were used in the Lithuanian population survey. In this survey, the authors applied the following scales: Flourishing Scale; The Satisfaction with Life Scale; The Cantril Self-Anchoring Striving Scale and The Positive and Negative Emotional Experience Scale. Results: The results of the study showed statistically significant differences in psychological well-being (psychological flourishing, life satisfaction, happiness, positive and negative emotional experiences) between different income quintile groups, with average psychological well-being constructs in the lowest income quintile being about twice lower than in the highest income quintile. The study showed that the mean ranks of the happiness score in the most deprived group were almost seven times lower than in the middle class. Conclusion: The research has established that strong and lasting negative emotional experiences are related to diminished well-being and can cause direct and indirect public damages. Authors indicate that additional research is needed.